Meningkatan Keterampilan Motorik Halus Melalui Kegiatan Mengancing Baju pada Siswa Cerebral Palsy di SLB YPAC Manado - Veybe Mamarimbing (Peneliti.net, 2021)
The purpose of this study was to get an overview and find out how the effectiveness of buttoning clothes in improving the fine motor skills of Cerebral Palsy students at SLB YPAC Manado. The research method used is single subject research using the A-B-A design, data is collected by means of observation using observation sheets, then the data is analyzed using visual graph analysis techniques, then the data is analyzed based on the components in each condition (A-B-A). Analyzes were carried out in conditions and between conditions. The results showed that from six sessions in the intervention phase, and three sessions in the baseline-2 phase, the average score of fine motor skills at baseline -1 was smaller, namely 36.67%, from the intervention phase it got 81.67%. Whereas in the baseline phase -2 the average score was 70%, this data certainly illustrates that the fine motor skills of cerebral palsy students increased after being given intervention through buttoning clothes. These skills really help students in everyday dress and are able to improve students' fine motor skills.